Factores Sociales, neuropsicológicos, neuroquímicos y neuroendocrinos asociados al comportamiento del agresor sexual - Navarro Jaramillo, Celeste Michaela (2023)
ABSTRACT: The current work is a literature review that argues the social, neuropsychological, neurochemical and neuroendocrine factors associated with sex offender behavior. The research was bibliographic, quantitative, cross-sectional and descriptive. Sixty-four documents were chosen to address the objectives of this research after the analysis with selection criteria and the methodological quality matrix (CRF-QS) was completed. Among the pertinent findings, it is noted that sexual aggressors have a history of abuse and domestic violence. On the neuropsychological level, abnormalities in the prefrontal cortex and the limbic system are recognized, making them more likely to engage in impulsive behaviors. Serotonin, dopamine, and oxytocin levels rose in the study of neurochemistry and were linked to violent sexual behavior and low empathy, while testosterone levels rose in the study of neuroendocrinology and were linked to increased desire and aversive sexual behaviors. These results lead to infer that the treatment of sexual offenders should be comprehensive.